Esophago-jejunal fistula closure using an over-the-scope clip: a case report - Arango Molano, Lázaro (2024)
sophago-jejunal anastomoses fistula could be mortal. Currently there is a wide therapeutic measure ranging from conservative management, endoscopic therapy and surgery. Endoscopic management has been positioned above other strategies due to minimal invasion which improves survival and reduces mortality. The endoscopic treatment of esophagojejunal fistulas can be varied with numerous techniques described to achieve their closure. These techniques include the placement of covered or partially covered self-expanding stents, the use of metal clips, alone or assisted by the loop technique, the use of endoscopic closed subatmospheric pressure therapy and, more recently, the use of endoscopic suture. In our service we use the techniques according to the characteristics of the fistula. In the case presented, it was decided, at the time of the endoscopy, to use clips with the help of a Cap to facilitate the technique and in the terminal closure angle, given the redundant tissue that was difficult to approach, we chose to place a clip Padlock®; With this, closure of the lesion was achieved in a few days with excellent clinical outcomes.